2018
DOI: 10.1177/2151459318806443
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Early Management of Pain in Hip Fractures: The Impact of Paracetamol

Abstract: Introduction:As the number of patients sustaining hip fractures increases, interventions aimed at improving patient comfort and reducing complication burden acquire increased importance. Frailty, cognitive impairment, and difficulty in assessing pain control characterize this population. In order to inform future care, a review of pain assessment and the use of preoperative intravenous paracetamol (IVP) is presented.Materials and Methods:Systematic review of preoperative IVP administration in patients presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
(103 reference statements)
0
18
0
4
Order By: Relevance
“…This contrasts directly with the association of cognitive impairment with other areas of perioperative management, namely, pain control, whereby patients with cognitive impairment are known to receive poorer pain management. 14 We found that there was no meaningful difference in nutritional practice in the presence of cognitive impairment, suggesting that cognitively impaired hip fracture patients receive comparable nutritional management to cognitively intact patients.…”
Section: Discussionmentioning
confidence: 65%
“…This contrasts directly with the association of cognitive impairment with other areas of perioperative management, namely, pain control, whereby patients with cognitive impairment are known to receive poorer pain management. 14 We found that there was no meaningful difference in nutritional practice in the presence of cognitive impairment, suggesting that cognitively impaired hip fracture patients receive comparable nutritional management to cognitively intact patients.…”
Section: Discussionmentioning
confidence: 65%
“…We identified 3570 potentially relevant publications, of which 36 systematic reviews 15‐50 were ultimately included in our analysis (Box 1; , table 3). Of 112 publications deemed potentially eligible by abstract review, 76 were excluded after reviewing the full text (Box 1; , table 4); the conclusions of excluded reviews that covered the same topic as reviews included in our overview are summarised in , table 5.…”
Section: Resultsmentioning
confidence: 99%
“…The 36 reviews described treatment with paracetamol of 44 painful conditions in adults and children (Box 2). Twenty systematic reviews reported efficacy estimates that we included in our analysis, and we calculated efficacy estimates for 12 reviews; four reviews (paracetamol for treating neuropathic pain, 38 hip fracture, 41 chronic non‐cancer pain in children, 40 and cancer pain in adults 39 ) did not include evidence from RCTs. A comprehensive summary of the converted effect estimates is included in , table 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to myocardial infarction and myocardial ischemia, postoperative myocardial damage, which is largely caused by intraoperative hypotension, is a significant and underestimated problem. [5] Criteria for myocardial damage are an increase in highly sensitive troponin T (hsTnT) greater than 20 ng/l with or without symptoms of ischemia. Exceptions are cases where the increase in troponin is associated with other non-cardiac causes (sepsis, pulmonary embolism).…”
Section: Introductionmentioning
confidence: 99%